Water force and speed management: East sector of the Guayabo National Monument of Turrialba archeological site hydraulic system. - Arroyo Wong, María Gabriela (2020)
Received: 07-04-2020 Approved: 07-24-2020 The hydraulic system of the Guayabo National Monument archeological site extends beyond the architectural core where the “major system” is located, after its evacuation, the water is directed eastward through open pipes, in which it is possible to find evidence of structures designed to manage the force and speed of it until it flows into the Lajitas river.